2015
DOI: 10.1111/bph.13200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the inflammatory regulator A20 by gibberellic acid in airway epithelial cells

Abstract: Background and Purpose NF‐κB‐driven inflammation is negatively regulated by the zinc finger protein A20. Gibberellic acid (GA3) is a plant‐derived diterpenoid with documented anti‐inflammatory activity, which is reported to induce A20‐like zinc finger proteins in plants. Here, we sought to investigate the anti‐inflammatory effect of GA3 in airway epithelial cells and determine if the anti‐inflammatory action relates to A20 induction. Experimental Approach Primary nasal epithelial cells and a human bronchial ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Karakoline is a highly toxic plant diterpenoid (32), and the pharmacological effects of preparations of Aconitum roots are attributed to diterpenoid alkaloids (33). The antiinflammatory activity of gibberellin (GA 3 ), also a plant-derived diterpenoid, is mediated through A20 induction (24). We therefore selected ikarugamycin and quercetin for further studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karakoline is a highly toxic plant diterpenoid (32), and the pharmacological effects of preparations of Aconitum roots are attributed to diterpenoid alkaloids (33). The antiinflammatory activity of gibberellin (GA 3 ), also a plant-derived diterpenoid, is mediated through A20 induction (24). We therefore selected ikarugamycin and quercetin for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…GA 3 induced A20, reduced IL-8 secretion, stabilized cytosolic IkBα, and reduced NF-κB (p65) activation (24). Here we set out to identify additional compounds able to induce A20.…”
Section: Cf Airway Inflammationmentioning
confidence: 99%
“…Therefore, the apparent lack of A20 described in epithelial cells of patients with CF and asthma [23,40] has important implications for the overall immune responses in these chronic airway diseases. Not surprisingly, A20 has recently been identified as a target enzyme for new anti-inflammatory drugs [41,42].…”
Section: The Diverse Functions Of A20mentioning
confidence: 99%
“…Using airway epithelial cells (cell lines and primary cells from control subjects), we have previously shown that pharmacological induction of A20 through the plant diterpenoid gibberellin (GA 3 ) is antiinflammatory [42]. Furthermore, using an advanced bioinformatics approach that established the link between disease-specific gene expression and the gene modification through already licensed drugs, statistically significant connections Map (sscMap) [44] we were able to predict drugs already licenced for the use in humans, which through the process of drug repositioning could be made available to CF patients.…”
Section: A20 As a Target For Anti-inflammatory Drug Development In Cfmentioning
confidence: 99%
See 1 more Smart Citation